2019
DOI: 10.3390/ma12101702
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Lack of Cytotoxicity of Alkyl-Capped Silicon Quantum Dots Prepared from Porous Silicon

Abstract: Freely-dissolved silicon quantum dots were prepared by thermal hydrosilation of 1-undecene at high-porosity porous silicon under reflux in toluene. This reaction produces a suspension of alkyl-capped silicon quantum dots (alkyl SiQDs) with bright orange luminescence, a core Si nanocrystal diameter of about 2.5 nm and a total particle diameter of about 5 nm. Previous work has shown that these particles are rapidly endocytosed by malignant cell lines and have little or no acute toxicity as judged by the standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…The photostability of SiQDs with alkyl termination in CACO-2 cells has been reported. 44 Cells having alkylated SiQDs of up to 50 μg/mL could still be detected after 14 days. The photostability of SiQDs could also be investigated by photobleaching studies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The photostability of SiQDs with alkyl termination in CACO-2 cells has been reported. 44 Cells having alkylated SiQDs of up to 50 μg/mL could still be detected after 14 days. The photostability of SiQDs could also be investigated by photobleaching studies.…”
Section: Resultsmentioning
confidence: 97%
“…Similar efforts have been studied in other papers. The photostability of SiQDs with alkyl termination in CACO-2 cells has been reported . Cells having alkylated SiQDs of up to 50 μg/mL could still be detected after 14 days.…”
Section: Resultsmentioning
confidence: 97%
“…[49][50][51] Phatvej et al demonstrated an endocytosis pathway for alkyl-capped silicon quantum dots using various cell lines, including HeLa. 52 According to the references, SiQDs/F127 micelles are taken up by HeLa and Fibroblast cells via endocytosis. Aer endocytosis, the micelle will be localized in the early endosome and later translocation to late endosome.…”
Section: Cell Viability and Cellular Uptakementioning
confidence: 99%
“…A straightforward approach lately demonstrated to increase the water dispersibility and photostability of SiQDs requires encapsulation into mesoporous silica through a simple condensation reaction in which mesoporous silica dispersed in toluene is mixed with a SiQD solution in C 2 H 5 OH, followed by heating to 110 • C for reflux for 3 h. The resulting encapsulated SiQD has excellent hydrophilicity, good biocompatibility, low cytotoxicity, retains a high surface area, and exhibits better fluorescence stability in acidic solutions, making it ideally suited for biological applications (Huang et al, 2018;Phatvej et al, 2019). A procedure for obtaining SiQDs capped with an Si-C bonded alkyl layer by heating in an ultrahigh vacuum at 200 • C has been reported (Chao et al, 2007).…”
Section: Encapsulation In Mesoporous Silicamentioning
confidence: 99%